2020
DOI: 10.2147/phmt.s266720
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effectiveness of Action Observation Training on Upper Limb Motor Function in Children with Hemiplegic Cerebral Palsy: A Systematic Review of Randomized Controlled Trials</p>

Abstract: The purpose of this review was to evaluate and examine the current best evidence for the effectiveness of action observation therapy on upper limb function rehabilitation in children with hemiplegic cerebral palsy. A comprehensive search of literature published between September 2010 and May 2020 was conducted using the following electronic databases: PubMed, Google Scholar, the Physiotherapy Evidence Database (PEDro), EMBASE, Cochrane library, and Scopus. Only randomized controlled trials evaluating the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
(117 reference statements)
0
11
0
7
Order By: Relevance
“…Rehabilitation may be further optimized by implementing strategies that target visuomotor processes, and sensorimotor integration in particular, as both initial (mal) adaptation and recovery occur in visuomotor brain areas involved in forming sensorimotor representations. Visuomotor strategies that have been successfully applied in other neurological disorders include mirror visual feedback, 48 action observation, 49 and graded motor imagery. 50 Future research could focus on identifying rehabilitation strategies to effectively target cerebral mechanisms in NA and other peripheral nerve disorders.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…Rehabilitation may be further optimized by implementing strategies that target visuomotor processes, and sensorimotor integration in particular, as both initial (mal) adaptation and recovery occur in visuomotor brain areas involved in forming sensorimotor representations. Visuomotor strategies that have been successfully applied in other neurological disorders include mirror visual feedback, 48 action observation, 49 and graded motor imagery. 50 Future research could focus on identifying rehabilitation strategies to effectively target cerebral mechanisms in NA and other peripheral nerve disorders.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…HABIT-ILE is a 90-hour training intervention offered in a day camp model. Action-observation training shows promise for augmenting upper limb function training effects by having the infant or child mimic demonstrations of successful actions on an object via activation of the mirror neuron system [33]. However, insufficient evidence is available to support using action-observations in isolation or above other task-specific interventions [34].…”
Section: Motor Interventions To Improve Functionmentioning
confidence: 99%
“…24 Recently, two systematic reviews regarding the effectiveness of AOT in the UL rehabilitation of children with cerebral palsy were published: the first emphasises that the variability between studies does not lead to any clear conclusion regarding the effectiveness of this approach, 25 while the second suggests that AOT is a promising intervention for UL rehabilitation in children with UCP. 26 Standard AOT consists in the observation of a typically developed model (TDM); however, an important assumption of AOT is that the MNS activates when the visual description of the observed action is matched with its corresponding motor representation in the observer's brain (direct matching hypothesis). 27 In fact, it has been shown that while observed actions belonging to the behavioural repertoire of the observer are mapped on his/her motor system, 28 those that belong only to her/ his visual experience are only categorised based on visual characteristics, without inducing any motor resonance phenomenon in the observer's brain.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 24 Recently, two systematic reviews regarding the effectiveness of AOT in the UL rehabilitation of children with cerebral palsy were published: the first emphasises that the variability between studies does not lead to any clear conclusion regarding the effectiveness of this approach, 25 while the second suggests that AOT is a promising intervention for UL rehabilitation in children with UCP. 26 …”
Section: Introductionmentioning
confidence: 99%